Anti-hyperglycemic and liver protective effects of flavonoids from Psidium guajava L. (guava) leaf in diabetic mice. (June 2020) - Zhu, Xiaoai; Ouyang, Wen; Lan, Yaqi; Xiao, Hang; Tang, Lan; Liu, Guo; Feng, Konglong; Zhang, Liqun; Song, Mingyue; Cao, Yong
Abstract: Guava leaf flavonoids were obtained using a simple extraction method to evaluate their anti-hyperglycemic and liver protective effects with a high-fat diet and a low-dose streptozotocin induced diabetic mouse model. Flavonoids supplementation significantly decreased fasting plasma glucose, glucose tolerance, and the insulin resistance index in diabetic mice, lowered the serum total cholesterol, triacylglycerol, and low-density lipoprotein cholesterol compared to the diabetic control group (p < 0.05). Furthermore, guava leaf flavonoids significantly decreased the liver and kidney indexes, and improved hepatocyte morphology in diabetic mice. Taken together, these results showed that guava leaf flavonoids had significant anti-diabetic and liver protective activities in diabetic mice. This study could facilitate the development of hypoglycemic functional foods from guava leaves. Graphical abstract: Image 1 Highlights: The guava leaf flavonoids were obtained using a simple extraction method. The guava leaf flavonoids significantly improved abnormal glucose metabolism in diabetic mice. The guava leaf flavonoids significantly decreased the serum lipids in diabetic mice. The guava leaf flavonoids significantly improved hepatocyte morphology in diabetic mice.